Voices to the Younger Generation or False Hopes? A Claim for Political Responsibility and Societal Development - Shahinaz Khalil (Social Work and Society)
From a discourse analytical perspective, the article starts from the"traveling" knowledge career guidance (CG) takes while shifting from a European into the Middle East context of Egypt. In a multi-stakeholder-based assessment, adopting a transformative evaluation approach, and a complex multiperspectivity research design this study focuses on the outcomes of a CG program implemented by the the Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ). As empirical data of this multimethod and participatory evaluation show, the evaluated program has strong effects on self-concepts of students and teachers. Like the program, the participatory evaluation opens the space for youthsÂ´ voices and claims and shifts the"inner point of speaking" of students and teachers, supporting an individualizing subjectivation of the young generation, as well as carrying collective and societal potentials for democratizing educational, societal and organizational relationships. Policy then is asked to take up this generational claim to make educational and societal innovations happen.